2002
DOI: 10.1109/tvt.2002.1002506
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of axle-generator errors due to wheel slip and slide

Abstract: Significant errors of train axle generators (tachometers) are due to wheel slip and slide. In this paper, an algorithm is designed to compensate for these errors. The algorithm identifies the wheel slip and slide by examining the variation of the processed vehicle longitudinal acceleration. Whenever wheel slip/slide is identified, then the vehicle speed is adjusted if a certain condition is met. The adjustment is a simple linear interpolation between the two speed values recorded before and after wheel slip/sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…(14), we know that there are only two parameters C and P in LSSVM model need to be set before training. Similar to, model 2, the process of parameter updating for model 3 is shown as below: the new training data set will be added to train model 3 to get the updating parameters in Eq.…”
Section: Parameter Updating Methodsmentioning
confidence: 99%
“…(14), we know that there are only two parameters C and P in LSSVM model need to be set before training. Similar to, model 2, the process of parameter updating for model 3 is shown as below: the new training data set will be added to train model 3 to get the updating parameters in Eq.…”
Section: Parameter Updating Methodsmentioning
confidence: 99%
“…It is necessary to check if the velocity estimate from the tachometer is within the normal range in order to detect the slip and slide errors. In general, the slip and slide errors tend to occur when the train is accelerating, decelerating or moving along a curved track [11]. In HST, it has been found that the slip and slide errors can cause a position error of from tens of meters to hundreds of meters.…”
Section: Slip and Slide Detection Algorithmmentioning
confidence: 99%
“…As a good reference, velocity estimation from a GPS receiver is used to compare with tachometer readings and to detect the wheel slip and slide [6]. And in [11], the authors use a Kalman filter (KF) to estimate the velocity and acceleration of the train and propose a slip and slide detection (SSD) technique to compare tachometer readings with the estimated states. In a viewpoint, the previous studies on the SSD are based on a mere comparison to a reference value measured by a single sensor such as GPS or on the mutual comparison of tachometer readings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations